# 5 we get easily the following lemma 26 n t has

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: te the distribution of N (s). Lemma 2.2. N (s) has a Poisson distribution with mean s. Proof. Now N (s) = n if and only if Tn s &lt; Tn+1 ; i.e., the nth customer arrives before time s but the (n + 1)th after s. Breaking things down according to the value of Tn = t and noting that for Tn+1 &gt; s, we must have ⌧n+1 &gt; s t, and ⌧n+1 is independent of Tn , it follows that Zs P (N (s) = n) = fTn (t)P (tn+1 &gt; s t) dt 0 Plugging in (2.12) now, the last expression is Zs ( t)n 1 · e (s t) dt = et (n 1)! 0 Zs n s = e tn 1 dt = e (n 1)! 0 s ( s)n n! which proves the desired result. Since this is our ﬁrst mention of the Poisson distribution, we pause to derive some of its properties. Theorem 2.3. For any k 1 EX (X 1) · · · (X k + 1) = (2.13) k and hence var (X ) = Proof. X (X 1) · · · (X EX (X k + 1) = 0 if X k 1) · · · (X 1 X k + 1) = j e j! j =k = k 1 so 1 X j (j 1) · · · (j jk e (j j =k k )! = k + 1) k since the sum gives the total mass of the Poisson distribution. Using var (X ) = E (X (X 1)) + EX (EX )2 we conclude var (X ) = 2 + ( )2...
View Full Document

## This document was uploaded on 03/06/2014 for the course MATH 4740 at Cornell University (Engineering School).

Ask a homework question - tutors are online